Risk of severe hematologic toxicities in cancer patients treated with PARP inhibitors: a meta-analysis of randomized controlled trials - Zhou JX; Feng LJ; Zhang X (Dove Medical Press, 2017)
Jian xin Zhou,1,* Li jin Feng,2,* Xi Zhang3 1Department of Gynecology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing, 2Department of Pathology, Shanghai Tenth People’s Hospital, Tongji University, School of Medicine, Shanghai, 3Department of Radiation Oncology, Affiliated Hospital of Hebei University, Baoding, China *These authors contributed equally to this work Purpose: Hematologic toxicities, including neutropenia, thrombocytopenia, and anemia, are major adverse effects of PARP inhibitors (PARPis), but the incidence rate and overall risk has not been systematically studied. Therefore, we conducted a meta-analysis of published clinical trials to investigate the incidence and relative risks (RRs) of severe (high-grade) hematologic events in cancer patients treated with PARPis.Methods: PubMed, Embase, and oncology conference proceedings were searched for relevant studies. Eligible studies were Phase II and III randomized controlled trials (RCTs) of PARPis in cancer patients with adequate safety data on hematologic toxicities. The summary incidence, RRs, and 95% confidence intervals (CIs) were calculated.Results: A total of 2,479 patients from 12 RCTs revealed that the incidence of PARPi-associated severe hematologic toxicities was, respectively: neutropenia: 32.9% (95% CI, 20.5%–48.3%); thrombocytopenia: 15.9% (95% CI, 9.5%–25.4%), and anemia: 9.1% (95% CI, 5.1%–15.7%). Olaparib was associated with an increased risk of severe neutropenia. Veliparib was associated with an increased risk of severe neutropenia and thrombocytopenia. Niraparib was associated with an increased risk of severe thrombocytopenia, anemia, and neutropenia. When stratified by combination therapy, significantly increased risk of hematologic toxicities was observed for patients treated with PARPis monotherapy and PARPis combined with single-agent chemotherapy.Conclusion: Treatment with PARPis olaparib, veliparib, and niraparib is associated with a significant increase in the risk of hematologic toxicities in cancer patients, and frequent clinical monitoring should be emphasized when managing these PARPis. Keywords: hematologic toxicities, PARP inhibitors, cancer, meta-analysis, RCTs